Neural transplantation : an introduction - Freed, William J. (Cellular and molecular neuroscience series., 2000)
Although there are many scientific and philosophical reasons to study the brain, for William J. Freed, "the most compelling reason to study the brain is to be able to repair the brains of individuals with nervous system injury or disease." Advances in repairing the nervous system, as well as new data on brain development, growth, and plasticity, have revolutionized the field of brain research and given rise to the technology of brain tissue transplantation. In this book Freed discusses both what may and what may not be possible. The book covers two aspects of neural tissue transplantation research. One involves the transplantation of particular cells to repair or augment specific neuronal systems. This technique could be useful for such conditions as Parkinson's disease, Huntington's disease, chronic pain, and epilepsy. The other line of research concerns regeneration from injury, especially of the spinal cord. After providing basic background on transplantation, brain structure, and development, the book discusses Parkinson's disease, the use of transplants to influence localized brain functions, circuit reconstruction, and genetic engineering and other future technologies.